Look up: encouraging individuals to choose reality over virtuality - Poon, Angel; Tascon, Steven (My University, 2018)
This project focuses on finding ways to motivate and persuade people to spend less time on their electronic devices, and more time immersed in the present. Our socially responsible campaign aims to raise awareness surrounding the disconnection the digital age has created and the detrimental impacts it has on meaningful human relationships. Brainstorming and other ideation techniques were put into practice to ensure a wide variety of ideas were generated to effectively tackle our problem. Then, by applying a user-centered design approach, we conducted surveys, interviews, and contextual observations to better understand our user. Our team is half-way through the design process thus far, currently creating the visual identity for our campaign, as well as creating tangible objects to communicate our message to the public. The final stages of this project will include: creating an experimental design component where the user will have the opportunity to interact with the campaign, and a 3-minute video portraying our complete design process.
Presented on April 23, 2018 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: Internet; social interaction